“Free Speech” and “Offensive” Speech on Campus - Scott, Peter (International Higher Education, 2017)
Debates about free speech and academic freedom—and their limits—have become sharper but also more confused. Conservatives demand greater restrictions, but so too do radicals worried that offensive speech may disrupt campus communities. Universities have a special responsibility to secure the right balance between free expression and offensive speech.